Quality assurance of qualitative research: a review of the discourse - Reynolds Joanna; Kizito James; Ezumah Nkoli; Mangesho Peter; Allen Elizabeth; Chandler Clare (BMC, 2011)
Abstract Background Increasing demand for qualitative research within global health has emerged alongside increasing demand for demonstration of quality of research, in line with the evidence-based model of medicine. In quantitative health sciences research, in particular clinical trials, there exist clear and widely-recognised guidelines for conducting quality assurance of research. However, no comparable guidelines exist for qualitative research and although there are long-standing debates on what constitutes 'quality' in qualitative research, the concept of 'quality assurance' has not been explored widely. In acknowledgement of this gap, we sought to review discourses around quality assurance of qualitative research, as a first step towards developing guidance. Methods A range of databases, journals and grey literature sources were searched, and papers were included if they explicitly addressed quality assurance within a qualitative paradigm. A meta-narrative approach was used to review and synthesise the literature. Results Among the 37 papers included in the review, two dominant narratives were interpreted from the literature, reflecting contrasting approaches to quality assurance. The first focuses on demonstrating quality within research outputs; the second focuses on principles for quality practice throughout the research process. The second narrative appears to offer an approach to quality assurance that befits the values of qualitative research, emphasising the need to consider quality throughout the research process. Conclusions The paper identifies the strengths of the approaches represented in each narrative and recommend these are brought together in the development of a flexible framework to help qualitative researchers to define, apply and demonstrate principles of quality in their research.